Atorvastatin exerts inhibitory effect on endothelial senescence in hyperlipidemic rats through a mechanism involving down-regulation of miR-21-5p/203a-3p. (January 2018) - Zhang, Jie-Jie; Zhang, Yin-Zhuang; Peng, Jing-Jie; Li, Nian-Sheng; Xiong, Xiao-Ming; Ma, Qi-Lin; Luo, Xiu-Ju; Liu, Bin; Peng, Jun
Graphical abstract: Highlights: Atorvastatin inhibits endothelial senescence in hyperlipidemic rats. Atorvastatin inhibitsmitochondrial dysfunction in ox-LDL-induced senescent endothelial cells. Atorvastatinsuppressesthe expressionsof miR-21-5p and miR-203a-3p. Atorvastatin restores Drp1 expression and mitochondrial function throughdown-regulation ofmiR-21-5p and miR-203a-3p. Atorvastatin exerts a novel non-lipid effect besides its function in modulation of lipids. Abstract: Statins are reported to exert benefits on endothelial function through a mechanism involving in prevention of endothelial senescence. This study aims to explore whether atorvastatin exerts inhibitory effect on endothelial senescence in hyperlipidemic rats or ox-LDL-treated HUVECs through a mechanism involving suppress of miR-21-5p/203a-3p expression and their downstream pathway. The rats were fed with high-fat diet to establish a hyperlipidemic model, which showed an increase in plasma lipids and endothelial senescence, accompanied by the elevation in plasma levels of miR-21-5p/203a-3p, down-regulation of Drp1 and up-regulation of p53 in the aorta of hyperlipidemic rats; these phenomena were reversed by atorvastatin. Next, HUVECs were incubated with ox-LDL to establish a senescent model in vitro. Consistent with the finding in vivo, atorvastatin treatment decreased the level of miR-21-5p and miR-203a-3p in the ox-LDL-treated HUVECs, restored Drp1 expression and mitochondrial function, as well as suppressed p53 and p16 expression and endothelial senescence. Based on these observations, we conclude that atorvastatin exerts inhibitory effect on endothelial senescence in hyperlipidemic rats through a mechanism involving down-regulation of miR-21-5p/203a-3p, which leads to the restoration of Drp1 level and recovery of mitochondrial function. Our findings highlight a novel non-lipid effect for atorvastatin besides its function in modulation of lipids.